Individualised decision making: interpretation of risk for extremely preterm infants—a survey of UK neonatal professionals. Issue 3 (19th August 2021) - Wood, Katherine; Di Stefano, Lydia Mietta; Mactier, Helen; Bates, Sarah Elizabeth; Wilkinson, Dominic
Abstract : Background: The British Association of Perinatal Medicine (BAPM) published a revised framework for perinatal management of extremely preterm infants (EPIs) in 2019. We aimed to assess UK neonatal professionals' interpretation of elements of this framework, as well as the consistency of their estimates of outcome for EPIs. Methods: An online survey gave participants five cases involving anticipated extremely preterm birth with different favourable and unfavourable risk factors. Respondents were asked to assign a risk category and management option using the BAPM framework and to estimate the chance of survival if the baby received active resuscitation and the chance of severe disability if they survived. Results: Respondents were consistent in interpretation of risk categories. The majority would follow parental wishes about management. Management decisions did not always correspond with risk assessment, with less inclination to recommend palliative (comfort) care. There were wide estimates of survival or severe disability (5%–90%) with consultants providing lower estimates of severe disability than other groups. Conclusion: UK neonatal professionals deferred to parental wishes in the cases presented, indicating an emphasis on shared decision making. However, they did not necessarily use the risk stratification approach for management decisions. Variation in estimates of outcome raises questions about the accuracy of informed decision making and suggests support is needed for UK clinicians to incorporate risk factors into individualised counselling. There may be value in validating existing online risk calculators for UK infants or in developing a UK specific risk model. Abstract : Topical and important insight into the current state of play in the UK regarding active management at the limit of viability.